2010
DOI: 10.1111/j.1365-3148.2009.00987.x
|View full text |Cite
|
Sign up to set email alerts
|

The significance of repeat testing in Turkish blood donors screened with HBV, HCV and HIV immunoassays and the importance of S/CO ratios in the interpretation of HCV/HIV screening test results and as a determinant for further confirmatory testing

Abstract: The purpose of this study was to investigate the intra-assay correlations amongst initial reactive and repeat screening results used in enzyme immunoassays (EIAs) for hepatitis B virus (HBV), hepatitis C virus (HCV) and HIV in blood donors. This study evaluated the value of using the power of the signal to cut-off (S/CO) ratio index for confirming anti-HCV/HIV reactive screening results, thereby touching upon the utility of S/CO indices in determining whether further confirmatory testing was necessary. Screeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 8 publications
1
14
0
Order By: Relevance
“…Our results indicate that it is possible to define S/CO values for each ARCHITECT assay with a PPV that nears 100%, as already demonstrated by Kiely et al and by Acar et al for other assay systems. However, if these S/CO values were used to discriminate confirmed positive samples from BFP without confirmatory testing, a substantial percentage of specimens would be incorrectly classified.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our results indicate that it is possible to define S/CO values for each ARCHITECT assay with a PPV that nears 100%, as already demonstrated by Kiely et al and by Acar et al for other assay systems. However, if these S/CO values were used to discriminate confirmed positive samples from BFP without confirmatory testing, a substantial percentage of specimens would be incorrectly classified.…”
Section: Discussionsupporting
confidence: 86%
“…This approach has been employed in many previous studies on anti-HCV, and most of them have indeed demonstrated the relationship between high S/CO values and serological confirmation of anti-HCV positivity (9,(14)(15)(16)(17) and even with HCV viremia (14,18). Thus, a higher S/CO ratio for anti-HCV is deemed to guarantee a higher PPV, but the data on the other screening assays are less common (10,11,19), and we believe that ours is one of the first systematic attempts in this direction, although it has been carried out on a relatively small number of blood donations.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, two tests increase the cost of the screening unless a sequential screening strategy is used (Seed et al, 2003). Another solution would be to use the strength of antibody reactivity as predictive marker of true-positive results and viremia in asymptomatic HCV infected people (Acar et al, 2010; Contreras et al, 2010; Kiely et al, 2010; Stramer et al, 2012). Our results, from an admittedly small study, are in accordance with this last report since mean s/co ratios were significantly higher in viremic subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies with small samples have suggested a relationship between the S/CO ratio in HIV Ag/Ab assays and confirmed HIV infection or the HIV viral load (VL) (1,(6)(7)(8). As the somewhat time-consuming HIV WB test is the currently approved confirmatory test in Australia, we assessed the positive predictive value of the Abbott Combo assay in this low-prevalence population.…”
mentioning
confidence: 99%